Canthinone alkaloids are novel protein tyrosine phosphatase 1B inhibitors - Sasaki, Tatsunori; Li, Wei; Higai, Koji; Koike, Kazuo (Bioorganic & medicinal chemistry letters, 2015)
Considerable attention has been paid to protein tyrosine phosphatase 1B (PTP1B) inhibitors as a potential therapy for diabetes. Screening of a natural compound library resulted in six canthinone alkaloids, namely, picrasidine L (1), 3,4-dimethyl-canthin-5,6-dione (2), 4-ethyl-3-methyl-canthin-5,6-dione (3), eurycomine E (4), 5-methoxy-canthin-6-one (5), and 5-acethoxy-canthin-6-one (6), as novel PTP1B inhibitors. Among these, 1 is the competitive PTP1B inhibitor with the best inhibitory selectivity between PTP1B and other PTPs and was shown to promote activity in the insulin signaling pathway in cell-based assays. Molecular docking simulations and structure-activity relationship analysis of 1 will add to its potential as a lead compound in future anti-insulin-resistant drug developments.